2003
DOI: 10.1086/377455
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Origin and Virulence Genotype in Relation to Resistance to Fluoroquinolones and/or Extended‐Spectrum Cephalosporins and Cephamycins amongEscherichia coliIsolates from Animals and Humans

Abstract: In Escherichia coli infection, the implications of fluoroquinolone (FQ) and extended-spectrum cephalosporin plus cephamycin (AmpC) resistance for phylogenetic origin and virulence potential are undefined, as is the influence of ecological context on these associations. Accordingly, 106 E. coli isolates exhibiting FQ and/or AmpC resistance and 98 susceptible isolates were compared with regard to phylogenetic background and virulence profiles, stratified by host group (104 predominantly extraintestinal human iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
191
8
10

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(241 citation statements)
references
References 42 publications
32
191
8
10
Order By: Relevance
“…Phylogroups A and B1 are considered less virulent or even commensal compared to the B2 phylogroup and, to a lesser extent, the D phylogroup [47]. Moreover, A and B1 were described as the most frequently resistant to antibiotics, as shown in our results; indeed, it seems that there is a trade-off between antibiotic resistance, particularly to quinolones (ciprofloxacin), and virulence in E. coli [32].…”
Section: Discussionsupporting
confidence: 67%
“…Phylogroups A and B1 are considered less virulent or even commensal compared to the B2 phylogroup and, to a lesser extent, the D phylogroup [47]. Moreover, A and B1 were described as the most frequently resistant to antibiotics, as shown in our results; indeed, it seems that there is a trade-off between antibiotic resistance, particularly to quinolones (ciprofloxacin), and virulence in E. coli [32].…”
Section: Discussionsupporting
confidence: 67%
“…These results support the hypothesis that although virulence factors and antibiotic resistance may confer increased Þ tness for extraintestinal infections in humans, they may do so via mutually exclusive pathways and in distinct populations. 21 A rise in the number of virulence factors was associated with a decrease in the rate of ESBL production. A robust virulence factor repertoire may be essential for a pathogen to overcome intact host defences, whereas it may be unnecessary in a compromised host, where antibiotic resistance may provide a substantial advantage to the survival of the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…(Johnson & O'Bryan, 2004). The ExPEC (UPEC) status of the E. coli isolates was predicted based on the operational definition of ExPEC: 'presence of ¢2 of the abovementioned VAGs' (Johnson et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Also, Johnson et al (2003) have reported that among human clinical E. coli isolates, FQ and/or AmpC resistance was associated with a significant shift towards the non-B2 phylogenetic lineage as well as a reduced virulence profile. However, there is a paucity of data on the antibiotic-resistance profile, phylogeny and prevalence of specific virulence-associated genes (VAGs) among uropathogenic E. coli (UPEC) from HIV patients.…”
Section: Introductionmentioning
confidence: 99%